Comparison of the indirect fluorescent antibody test with agglutination, complement-fixation, and Coombs tests for Brucella antibody - Edwards, Joan M. B. (1970)
A comparison is made of a Brucella fluorescent antibody test with four standard tests on 342 normal, 86 diagnostic, and 41 known positive human sera. Where positive titres of accepted significance were obtained in standard tests, a titre of 1/10 or more was achieved in the fluorescence test.